Infant colic and feeding difficulties. Issue 10 (21st September 2004) - Miller-Loncar, C; Bigsby, R; High, P; Wallach, M; Lester, B
Abstract : Aims: To examine the relation between colic and feeding difficulties and their impact on parental functioning for a primarily clinic referred sample. Methods: Forty three infants (and their mothers) were enrolled between 6 and 8 weeks of age. Infants were divided into two groups, colic (n = 19) and comparison (n = 24), based on a modified Wessel rule of three criteria for colic. Families were assessed at two visits; one occurred in the laboratory and one occurred in a paediatric radiology office. Outcome measures included the clinical assessment of infant oral motor skills, behavioural observation of mother-infant feeding interactions, maternal questionnaires on infant crying, sleeping and feeding behaviours, and the occurrence of gastro-oesophageal reflux (GOR) in the infants using abdominal ultrasound. Results: Infants in the colic group displayed more difficulties with feeding; including disorganised feeding behaviours, less rhythmic nutritive and non-nutritive sucking, more discomfort following feedings, and lower responsiveness during feeding interactions. Infants in the colic group also had more evidence of GOR based on the number of reflux episodes on abdominal ultrasound as well as maternal report of reflux. Mothers in the colic group reported higher levels of parenting stress. Conclusions: Results provide the first systematic evidence of feeding problems in a subgroup of infants with colic. Data also illustrate the impact of these difficulties on parental and infant functioning. The association between feeding difficulties and colic suggests the potential for ongoing regulatory problems in infants presenting with clinically significant colic symptoms.